Refashioning pop music in Asia : cosmopolitan flows, political tempos, and aesthetic industries - Chun, Allen John Uck Lun, 1952-; Rossiter, Ned.; Shoesmith, Brian (London ; New York : RoutledgeCurzon, 2004)
This collection of thirteen essays examines cultural, political, economic, technological and institutional aspects of popular music across Asia, from India to Japan.
Capitalism and cultural relativity : the Thai pop industry, capitalism, and Western cultural values / Michael Hayes -- Popping the myth of Chinese rock / David Stokes -- World music, cultural heteroglossia and indigenous capital : overlapping frequencies in the emergence of cosmpolitanism in Taiwan / Allen Chun -- The imagined community of Maa Tujhe Salaam : the global and the local in the post-colonial / Rangan Chakravarty -- Global industry, national politics : popular music in 'new order' Indonesia / Krishna Sen and David T. Hill -- The case of the irritating song : Suman Chatterjee and modern Bengali music / Sudipto Chatterjee -- Magical mystical tourism : (debate dub version) / John Hutnyk -- 'Love never dies': romance and Christian symbolism in a Japanese rock video / Carolyn S. Stevens -- Japanese popular music in Hong Kong : what does TK present? / Masashi Ogawa -- Raising the ante of desire : foreign female singers in a Japanese pop music world / Christine R. Yano -- Pop music as post colonial nostalgia in Taiwan / Jeremy E. Taylor -- Popular music and interculturality : the dynamic presence of pop music in contemporary Balinese performance / Zachar Laskewicz.
Includes bibliographical references (pages 198-211) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Popular music -- Asia -- History and criticism; Popular music -- Social aspects -- Asia; Popular music -- Political aspects -- Asia; Musique populaire -- Asie -- Histoire et critique; Musique populaire -- Aspect social -- Asie; Musique populaire -- Aspect politique -- Asie; MUSIC -- Genres & Styles -- International; MUSIC -- Genres & Styles -- Pop Vocal; MUSIC -- Genres & Styles -- New Age; Popular music; Popular music -- Political aspects; Popular music -- Social aspects; Asia; Criticism, interpretation, etc